L’ethnobotanique au carrefour du Muséum national d’Histoire naturelle et du Musée ethnologique de Salagon (Alpes-de-Haute-Provence) - Carole Brousse (Revue d'ethnoécologie)
« Ethnobotanical workshop », « ethnobotanical excursion », « ethnobotanical garden », etc.: ethnobotany is trendy. Historically studied in the National Museum of Natural History and neglected by universities, this discipline is nowadays invested by community movements but also by the Ethnopôle de Salagon, a french institution, which organizes, since 2001 in the Alpes de Haute Provence, a seminar exclusively devoted to ethnobotany. Each year the Ethnopôle de Salagon trains a hundred of ethnobotanists. « Professional » or « amateur », all of them follow the steps of Pierre Lieutaghi - the most famous french ethnobotanist and historical founder of the garden’s ethnopôle. At the crossroads of the natural sciences and social sciences, ethnobotany do its training at the Ethnopôle de Salagon.